BERGSON, MOURNING AND MEMORY: THE FRAGILITY OF TIME IN KLAUS LANG'S TRAUERMUSIK. (21st June 2017) - Wilson, Daniel
Abstract: The music of composer Klaus Lang (b. 1971) is often overlooked in broader discussions of New Music in Europe, and is little discussed outside of his native Austria. When his music is discussed, it is usually in relation to its fragile textures and extreme quietness. However, the notion of time in its various guises also plays a key role in Lang's work, and it is the scale and structure rather than volume and timbre of his music that this article probes. This paper looks at the construction and configuration of time in Lang's music utilising the writings of Henri Bergson, and specifically the notion of duration as a mediation of time and consciousness. I suggest that Lang's work is predicated on the fragile balancing of conscious and 'clock' time, creating structures that destabilise our perception of temporality in his work.